귀밑샘의 형질세포와 호산성 조직구를 다량 함유한 림프절외 변연부 B-세포 림프종의 세침흡인 세포검사 소견 -1예 보고 - 이영석; 안정석; 채양석; 염범우; 최종상; 김철환; Lee, Young-Seok; An, Jung-Suk; Chae, Yang-Seok; Yeom, Bom-Woo; Choi, Jong-Sang; Kim, Chul-Hwan (Taehan Sepo Pyŏngri Hakhoe chi, 2007)
The authors present the fine needle aspiration cytology (FNAC) cytologic findings of a case of extranodal marginal zone B cell lymphoma (MZBCL), which featured abundant plasma cells and eosinophilic histiocytes arising in both parotid glands. A 49-year-old female presented with palpable masses in both parotid glands. She had been suffering from systemic lupus erythematosus and rheumatoid arthritis. The lesions were evaluated by FNAC and smears showed a small number of clusters of oncocytic cells with abundant eosinophilic granular cytoplasm and small nuclei, intermixed with small to medium-sized lymphoid cells containing round to lobulated nuclei, which suggested Warthin's tumor. Some of lymphoid cells had a plasmacytoid appearance, and some scattered large cells contained a large amount of eosinophilic cytoplasm. Bilateral superficial parotidectomy was performed and a histopathologic study indicated MZBCL with abundant plasma cells, intermixed with eosinophilic histiocytes. The presence of oncocytic cells and a mixture of lymphoid and plasma cells indicates Warthin's tumor, but the cytologic features of a relatively monotonous small to medium-sized lymphoid infiltrate suggest the possibility of MZBCL in the clinical setting of an FNAC study performed on a patient suffering from a connective tissue disease.